2016
DOI: 10.1002/jmri.25244
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal lymphatic systems: Evaluation using spectral presaturation with inversion recovery T2‐weighted MR images with 3D volume isotropic turbo spin‐echo acquisition at 3.0T

Abstract: The findings of this study support the feasibility of SPIR T2 -weighted MR images with 3D-VISTA at 3.0T for evaluating the perirenal lymphatic systems. J. MAGN. RESON. IMAGING 2016;44:897-905.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For instance, renal cell carcinoma can spread via lymphatic drainage from the kidney to the paraaortic lymphatics, and systemic malignancies such as lung and stomach carcinomas can find their way to the kidney via the lymphatic vessels. Hence, evaluation of the perinephric lymphatics by images such as MRI is of clinical importance when evaluating those conditions [10]. The lymphatics also play a critical role after kidney transplantation since lymphoceles and lymphorrhea can develop especially with the common use of steroids and mTOR inhibitors for immunosuppression following transplantation increasing the risk of renal allograft rejection [11].…”
Section: Anatomy and Histology Of The Kidney Vasculaturementioning
confidence: 99%
“…For instance, renal cell carcinoma can spread via lymphatic drainage from the kidney to the paraaortic lymphatics, and systemic malignancies such as lung and stomach carcinomas can find their way to the kidney via the lymphatic vessels. Hence, evaluation of the perinephric lymphatics by images such as MRI is of clinical importance when evaluating those conditions [10]. The lymphatics also play a critical role after kidney transplantation since lymphoceles and lymphorrhea can develop especially with the common use of steroids and mTOR inhibitors for immunosuppression following transplantation increasing the risk of renal allograft rejection [11].…”
Section: Anatomy and Histology Of The Kidney Vasculaturementioning
confidence: 99%
“…The renal hilar lymphatics involve adrenal glands [32]. Matsumoto et al [33] reported that by using a heavily T2-weighted three-dimensional MRI sequence, these lymphatic vessels can be frequently and clearly identified, with the highest detectability in the renal hilar lymphatics, which involve the adrenal glands [32]. These anatomical features may explain the following unexplained characteristics in TAFRO syndrome: first, paraaortic edema and perirenal edema were observed in almost all cases in patients with early stage TAFRO syndrome, even in those without pleural effusion or ascites [7].…”
Section: Discussionmentioning
confidence: 99%